A Human Rights Approach to Development: Some Practical Implications for Water Aid’s Work - Hausermann, Julia (Water Nepal, 2003)
This paper was presented at a conference organized by Water Aid in 1998. The paper analyzes of a human rights approach to development, and exploration of its benefits and its practical implication for work of agencies supplying water. What is the value added by this approach? The paper shall end with a few tentative recommendations for water and sanitation work. Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.127-149